Impact of Direct and Indirect Cat Allergen Exposure Patterns on Allergic Rhinitis and Asthma in Cat-Sensitized Patients - Osman Ozan Yegit (Haseki Tıp Bülteni, 2023)

(untitled)
Aim:Cat allergen hypersensitivity is a clinical condition that can affect patients across a wide spectrum, ranging from mild allergic rhinitis to severe asthma. Since cat hypersensitivity can occur through indirect exposure, non-cat owners also have the risk of developing cat allergies. The aim of this study was to investigate the effects of direct and indirect exposure patterns on the clinical features of allergic rhinitis and allergic asthma in patients with cat hypersensitivity.Methods:In our study, designed as a retrospective cohort, the demographic and clinical characteristics of 257 patients diagnosed with cat allergy and allergic rhinitis who were followed up and treated between January 2022 and March 2023 were evaluated. Cat and non-cat owner patients were compared in terms of symptoms of allergic rhinitis, treatment steps for allergic rhinitis, and frequency, control and treatment steps for allergic asthma.Results:The median (interquartile range) age of the patients was 29 (23-38), and 182 of them were female (70.8%). The visual analogue scale symptom scores of cat owners were significantly higher than those of non-cat owners (p=0.022 and p=0.023, respectively). The rate of moderate or severe allergic rhinitis that persisted despite treatment was higher in cat owners (31.8%) than in non-cat owners (17.8%). Additionally, allergic asthma frequency in cat owners with moderate or severe allergic rhinitis symptoms despite medical treatment was more common than in cat owners with mild rhinitis (p=0.026).Conclusion:Direct exposure to cat allergens is associated with poor control of allergic rhinitis symptoms. These patients should avoid contact with cats. If avoidance is not possible, the clinical condition of these patients should be closely monitored, as they may have treatment-resistant respiratory allergies.